The values of systemic immune-inflammation index and neutrophil-lymphocyte ratio in predicting testicular germ cell tumors: A retrospective clinical study - Wang, Shuo; Yang, Xiao; Yu, Ziyi; Du, Peng; Cao, Yudong; Ji, Yongpeng; Ma, Jinchao; Yang, Yong (Frontiers in Oncology, 2022)
Purpose To determine whether complete blood count (CBC) based inflammatory parameters can be used as markers predicting testicular germ cell tumors (GCTs). Material and methods Between 2013 to 2018 the data of 58 patients with testicular GCTs undergoing radical orchiectomy and 54 malignancy-free healthy men were retrospectively analyzed as tumor group and control group. Patient baseline characteristics including age, pathological stage and pre-surgery CBC based inflammatory parameters including neutrophil/lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR), lymphocyte/monocyte ratio (LMR), systemic immune-inflammation index (SII), lymphocyte ratio (LR), neutrophil ratio (NR), mean platelet volume (MPV) and red cell distribution (RDW) were analyzed and compared between tumor group and control group. Receiver operating characteristic (ROC) curve were used analyzing data with significantly difference to assess the discriminative ability of the markers for GCTs, area under the curve (AUC), cut-off value, sensitivity and specificity were calculated. The binary logistic regression model was used to evaluate the association between significant inflammatory markers and risk of GCTs. Results Mean age of the tumor and control group was 41.1±15.36 and 44.89±9.2 years, respectively. Mean NLR, SII and RDW were significantly higher in tumor group compared with control group with P=0.005, P=0.001 and P=0.016, respectively. The cut-off value for NLR, SII and RDW were found as 3.38 (AUC: 0.704, sensitivity=51.4%, specificity=88.6%, P=0.003), 881.24 (AUC: 0.725, sensitivity=45.7%, specificity=91.4%, P=0.001) and 0.14 (AUC: 0.63, sensitivity=28.6%, specificity=97%, P=0.063), respectively. Patients were divided into two groups according to the threshold values. By using the multivariable logistic regression models, NLR ≥ 3.38 (OR, 5.86; 95% CI, 1.67-20.65, P=0.006) and SII ≥ 881.24 (OR, 4.89; 95% CI, 1.48-15.32, P=0.009) were independent risk factors predicting GCTs. Significantly statistical difference of pathological stage was also found between groups with respect to NLR cut-off values (P=0.034) and SII cut-off values (P=0.049). Conclusion As the CBC based inflammation parameters, both NLR and SII could be used as effective tumor markers predicting the GCTs, and higher NLR and SII are associated with higher pathological stage. In addition, SII is a more powerful tool among these two inflammatory markers.